تطبيق كتاب "المحادثات العربية" لتنمية مهارة الكلام لدى طلاب الصف السابع بمدرسة المنورة المتوسطة الإسلامية جومبانج - Rifqi Ahmada; M. Burhanuddin Ubaidillah (Al-Fakkaar, 2026)
This research aims to describe the implementation of Muhadatsah Arabiyah in developing students’ speaking skills and to identify the supporting and inhibiting factors at MTs Al-Munawwarah. This study employed a descriptive qualitative approach using observation, interviews, and documentation for data collection. The findings showed that the implementation was conducted through planning, implementation, and evaluation stages. The learning process emphasized dialogue memorization, guided conversation, and contextual communication activities, enabling students to gradually improve their confidence, vocabulary mastery, and communicative ability in Arabic. The effectiveness of the implementation was supported by the interaction of a conducive language environment, communicative teaching methods, contextual learning materials, and students’ motivation. Meanwhile, limited vocabulary mastery, the less optimal physical design of the textbook, and demanding vocabulary targets became the main inhibiting factors. This study concludes that speaking skill development depends not only on the textbook itself but also on its integration with a supportive language environment and communicative learning practices, contributing practical insights for Arabic language teaching at the MTs level.